Rural Migration in the Developing Economy and its Reflection on the Urban Structure (with Reference to Kurdistan Region) - Hoshiar Marouf (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Indeed ,a lot of common lines bringing different experiences of the developing countries (in respect to rural migration) that are closed to each other, however each experience has its special characteristics which are not necessarily congruent to other experiences as has really been taken place during 1980s in Kurdistan region. To deal with practical aspects of urbanization in Kurdistan region, a simple questionnaire conducted in two urban areas; Sulaimany (city) and Koya (town). The questions were immediately related to the prospected causes and consequences of migration and urban localization. The research directed to test (qualitatively with reference to the questionnaire results) a principal assumption ;( aversion of migration and urban attractions, both of them resulted in a dichotomous process of settlement). In so far this paper concentrated on the following subjects; One – Rural centrifugal forces of migration. Two –Governmental Obligatory and Urban centripetal forces of migration. Three- Urbanization and immigration consequences. Four – Towards a sound urbanization in the developing economy. Lastly, the paper concluded that after a long and sluggish rural migration in Iraq during 1950s, 1960s and 1970s governmental obligatory forces in the second half of 1980s represented the most decisive and profoundly determinants of the rural migration in the IKRand this , as a basic consequence , entails a chronic restless to reside between the village and the city